Analisis Pengaruh Harga, Kualitas Produk dan Iklan Terhadap Keputusan Pembelian Kosmetik Wardah (Studi pada Mahasiswi Universitas Muhammadiyah Surakarta) - Putri, Ela Karisma; , Basworo Dibyo, S.E, M.Si (2016)
In the face of increasingly intense marketing competition, a producer should not be fixated in the form of products that offer the benefits of the base. Companies must be able to know what is needed and expected by consumers. The emergence of overseas cosmetics industry competition tightened the competition Indonesian cosmetic industry. The purpose of this study was to determine the influence of Price, Quality Products and cosmetic advertisement of the Purchase Decision Wardah in Surakarta Muhammadiyah University student. After review of the literature and formulation of hypotheses, data were collected through questionnaire method on 100 respondents Surakarta Muhammadiyah University student who uses cosmetics Wardah that taken by purposive sampling. The Multiple analysis results ie, Y = 0,199X1 + 0,215X2 + 0,285X3. The independent variables that most influence on the dependent variable is variable of advertisement (0.285), followed by a variable price (0,199) and the variable quality of the final product (0.215). T test results prove that all independent variables (Price, Quality Products and rent) have a positive effect on the dependent variable ie Purchasing Decisions Cosmetics Wardah in Surakarta Muhammadiyah University student. Data coefficient of determination (adjusted R2) obtained at 0,211. This means that 21.1% purchase decision can be explained by the independent variable, while the remaining 78.9% is influenced by other variables not examined in this study.